1 Answers

Best Answer

Step 1

The given two polynomials to add are 9x+6 and 5x−3

When we add two polynomials, then the coefficients of the like terms get added together and the constants get added together.

Step 2

On simplifying the given polynomial, we get

(9x+6)+(5x-3)=9x+6+5x-3

=9x+5x+6-3

=(9+5)x+3

=14x+3

Therefore, the sum of the two polynomials is 14x+3

The given two polynomials to add are 9x+6 and 5x−3

When we add two polynomials, then the coefficients of the like terms get added together and the constants get added together.

Step 2

On simplifying the given polynomial, we get

(9x+6)+(5x-3)=9x+6+5x-3

=9x+5x+6-3

=(9+5)x+3

=14x+3

Therefore, the sum of the two polynomials is 14x+3